Study of the nonlinear control techniques for single acting VGT pneumatic actuator - Laghrouche, Salah; Mehmood, Adeel; El Bagdouri, Muhammad (International Journal of Vehicle Design, 2012)
In this paper, we have developed a detailed mathematical model of a pneumatic actuator for a Variable Geometry Turbocharger (VGT) equipped with an Electro-pneumatic Pressure Converter (EPC). This model may require complex calculations for control purpose; therefore the dynamics of the EPC have been neglected and replaced by a static gain. These models incorporate friction and aerodynamic force related effects by using adaptive LuGre model. To compensate for parametric uncertainties, two single-input single-output nonlinear position control laws are designed using the second order sliding mode (SMC) and backstepping control. A comparative study with experiments shows the effectiveness of the proposed controllers. Copyright © 2012 Inderscience Enterprises Ltd.
Keywords: Mathematical modelling; Adaptive LuGre model; Sliding mode control; SMC; Twisting algorithm; Backstepping control; Nonlinear control; VGT pneumatic actuators; Variable geometry turbocharger; Electropneumatic pressure converter; EPC; Friction; Aerodynamics; Parametric uncertainties; Position control; Vehicle design